Turkey’s Transitions : Integration, Inclusion, Institutions - World Bank (Washington, DC, 2014)
Turkey has always been a country of strategic significance. Its geographic position as a bridge between East and West, its long and unique history of relations with the European Union (EU), and the particular rout the Republic of Turkey chose towards modernization after its foundation in 1923 have attracted the attention of historian and political scientists a like. More recently, Turkey’s economic success has become a source of inspiration for a number of developing countries, particularly – but no only – in the Muslim world. Over the last two years, however, questions have emerged over the lessons to be drawn from Turkey’s experience. Economic growth has come down to a modest 3-4% range - from well over 5% during 2002-2011 - and risks related to the country’s large external financing needs have not been banished. Critics have raised questions over the strength of Turkey’s legal and economic institutions, and economists are concerned that Turkey may remain ‘trapped’ in its current middle income status. This publication is addressed to policy makers both from other emerging markets and from Turkey itself. To the former, if offers lessons in how Turkey progressed towards international integration and increased social inclusion. To the latter, it offers a narrative of the country’s achievements and remaining challenges that may help define the reform agenda going forward.